Mathematical Frameworks for Component Software : Models for Analysis and Synthesis. - Liu, Zhiming (Series on component-based software development., 2006)
The range of components technology is both wide and diverse, but some common understanding is emerging through the ideas of model-based development. These include the notions of interfaces, contracts, services, connectors and architectures. Key issues in the application of the technology are becoming clearer, including the consistent integration of different views of a component, component composition, component coordination and transformation for platforms. However, we still know little about theories that support analysis and synthesis of component-based systems. The distinct feature of this.